Malaysian undergraduates' knowledge and opinions on early childhood oral health - Mani, Shani Ann; Burhanudin, Nor Aszlitah; John, Jacob (Pub Med, 2012)
Aim in Malaysia, Early Childhood Caries (ECC) was found to affect 76.2% of 5-year-olds (2005). General practitioners are more likely to encounter preschool children and are in a better position to educate parents and caretakers about ECC and make appropriate referrals. This study assessed the knowledge and opinions on early childhood oral health among medical and dental undergraduates. Methods This cross sectional study involved 245 students enrolled in the first year medical (M1) and dental (D1) course and fourth year medical (M4) and dental (D4) course. The students completed a self-administered questionnaire which included knowledge and opinions on early childhood oral health. Comparisons between the groups were done using chi-square test. results Dental students showed significantly better knowledge than medical students. D1 students showed significantly better knowledge of age of first tooth eruption over M1. Knowledge of recommended age for bottle weaning was higher among D4 students but not significantly more than M4 students. conclusion The majority of medical students showed inadequate knowledge indicating that medical curriculum should emphasise on oral health topics of public health relevance like ECC and its prevention. Dental students had better knowledge regarding early childhood oral health, but lacked knowledge on its preventive aspects.